The upper Miocene chitons of northwest France (Mollusca: Polyplacophora) - Dell’angelo, Bruno; Landau, Bernard M.; van Dingenen, Frank; Ceulemans, Luc (Zootaxa, 2018)
This study describes the chiton fauna (Mollusca, Polyplacophora) from the upper Miocene Tortonian deposits of northwest France previously known as the ‘Redonian’. Twenty-two species were identified (represented by 9,380 valves), of which seven were already known, one is assigned at generic level (Leptochiton sp.) and 14 are described as new (Lepidopleurus pseudobenoisti sp. nov., L. gallicus sp. nov., Leptochiton parvus sp. nov., Leptochiton lateropustulosus sp. nov., Leptochiton renauleauensis sp. nov., Hanleya sancticlementensis sp. nov., H. sossoi sp. nov., Ischnochiton nitidum sp. nov., Callochiton pouweri sp. nov., Rhyssoplax assurrectum sp. nov., Tonicella redoniensis sp. nov., Acanthochitona globosa sp. nov., A. andegavensis sp. nov. and A. chauvereauensis sp. nov.). Regarding the stratigraphic distribution of the 21 taxa identified, 15 are restricted to the Miocene, the remaining six are extant and are distributed in the Atlantic and Mediterranean (Lepidopleurus cajetanus, Leptochiton algesirensis, Hanleya hanleyi, Ischnochiton rissoi, Callochiton doriae and Rhyssoplax corallinus. The number of new species is high (14 out of 22), possibly explained in part by the fact that this is the first description of the northwestern French upper Miocene chiton fauna - true endemicity is less likely in the light of scarce sampling.